Blockade of PD-1 Signaling Enhances Th2 Cell Responses and Aggravates Liver Immunopathology in Mice with Schistosomiasis japonica. - Sha Zhou; Xin Jin; Yalin Li; Wei Li; Xiaojun Chen; Lei Xu; Jifeng Zhu; Zhipeng Xu; Yang Zhang; Feng Liu; Chuan Su (Public Library of Science (PLoS), 2016)
BACKGROUND:More than 220 million people worldwide are chronically infected with schistosomes, causing severe disease or even death. The major pathological damage occurring in schistosomiasis is attributable to the granulomatous inflammatory response and liver fibrosis induced by schistosome eggs. The inflammatory response is tightly controlled and parallels immunosuppressive regulation, constantly maintaining immune homeostasis and limiting excessive immunopathologic damage in important host organs. It is well known that the activation of programmed death 1 (PD-1) signaling causes a significant suppression of T cell function. However, the roles of PD-1 signaling in modulating CD4+ T cell responses and immunopathology during schistosome infection, have yet to be defined. METHODOLOGY/PRINCIPAL FINDINGS:Here, we show that PD-1 is upregulated in CD4+ T cells in Schistosoma japonicum (S. japonicum)-infected patients. We also show the upregulation of PD-1 expression in CD4+ T cells in the spleens, mesenteric lymph nodes, and livers of mice with S. japonicum infection. Finally, we found that the blockade of PD-1 signaling enhanced CD4+ T helper 2 (Th2) cell responses and led to more severe liver immunopathology in mice with S. japonicum infection, without a reduction of egg production or deposition in the host liver. CONCLUSIONS/SIGNIFICANCE:Overall, our study suggests that PD-1 signaling is specifically induced to control Th2-associated inflammatory responses during schistosome infection and is beneficial to the development of PD-1-based control of liver immunopathology.